Tuberculous Empyema Necessitatis in a 40-Year-Old Immunocompetent Male - Farhang Babamahmoodi; Lotfollah Davoodi; Roya Sheikholeslami; Fatemeh Ahangarkani (Case Reports in Infectious Diseases)
Empyema necessitans (EN) is a kind of empyema that diffuses to extrapleural space and can involve chest pain. Tuberculosis (TB) is the most common cause of EN. This disease can be found in both immunocompromised and immunocompetent individuals but is usually seen in the immunocompromised individuals. Because of long duration and ambiguous symptoms of the disease, diagnosis can be hard. The disease can be treated both medically and surgically. Missing the disease can lead to undesirable effects on patient’s condition and health care setting. This problem can be seen in endemic area in which controlling of TB is hard. Report of the disease in local health care center for desirable treatment and health maintenance is necessary. We explained a rare case of pulmonary TB in a patient that was healthy in other fields and just showed the minimum systemic symptoms. The patient came with a mass in lower part of back of chest cage, with a mild pain. The imaging survey showed EN. Smear and Ziehl-Neelsen stains from subcutaneous aspiration were positive for TB. This case showed importance of clinical view and awareness of this silent but serious disease in endemic area especially for TB.